Gender Pedagogy: A Feminist Approach to Teaching Sexist, Women Solidarity, and Power in the Patience Stone - Suci Suryani; Fabiola D. Kurnia; Pratiwi Retnaningdyah (IJORER : International Journal of Recent Educational Research, 2023)
Objective: The study aims to examine what gender issues in the novel are learned and how those issues get responses from the students. Method: The data acquisition method in this study is selecting the author's narration, the monolog, and dialog in the novel, showing the gender issues based on bell hooks' perspective on sexist oppression, women's solidarity, and power and asking thirty-five students in the class of their response concerning the issues. Result: The result shows the students will learn that the unnamed female protagonist experiences sexist oppression, obtains women's solidarity from her aunt, exercises her power to resist her husband's cruelty, and compares the issues to the surrounding phenomena. Novelty: Some previous studies have analyzed gender inequality in The Patience Stone, gender pedagogy leading to building higher students' gender awareness by teaching gender through a novel has been rarely concerned. Hence, the study promotes teaching gender through The Patience Stone and another similar novel in higher education to build students' awareness concerning gender issues and invite their critical response towards gender problems in the novel and real life.